Excessive Deadly Addiction Chewing Betel Quid as a double burden, For Poverty Community Kupang Regency, West Timor - Kloee Titu Eki, Ardent; Ngadilah, Christina (Green Publisher Indonesia, 2023)
People's lives in developed countries are indeed in contrast to developing countries as well as in terms of behavior. Betel nut is estimated to be consumed by 10% -25% of the world's population. In East Nusa Tenggara, Indonesia, almost the entire population (21) districts consume betel nut, including the elderly, young people and school children, even those who are still studying in Early Education. About 80% of the population of Kupang Regency, West Timor, consume betel nut.even though the district Kupang is mostly poor. Possible Hazards in areca nut mixed with various other ingredients such as betel nut and lime produce adverse health effects including oral cancer and other systemic diseases, as well as having the potential for dependence such as smoking and alcohol. We conducted a survey of traditional leaders and community leaders who have been addicted to consuming betel nut for more than 20 years in Kab. Kupang West Timor in a poor community. A total of 10 participants conducted in-depth interviews regarding events using betel nut, related to customs and culture, and their relationship to health. It was stated by WHO that areca nut is a psychoactive substance and is a class 1 carcinogen. According to the community, consuming betel nut is exciting and has nothing to do with any disease. No one agrees to stop consuming betel Nut, and mostly do not agree to prevent children from consuming betel nut from an early age.